Rancang Bangun Alat Proses Fermentasi Kedelai Menggunakan Kendali Suhu Dan Kelembaban Untuk Produksi Tempe Skala Kecil - Yusuf Ismail Nakhoda; Aryuanto Soetedjo; Pravasta Ongko S (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Teknologi Nasional Malang, 2020)
In making tempeh, the fermentation process is an important process. The fermentation process of tempeh really determines the quality of the tempe produced. In the conventional method, the temperature and humidity in the tempe fermentation process are not regulated, so the fermentation results are strongly influenced by the weather. In general, the fermentation process for tempeh takes about one and a half days. With technological advances in electronics, temperature and humidity can be controlled according to the desired range. By utilizing temperature and humidity controllers in the tempe fermentation process, the time of making tempe can be accelerated without reducing the quality of the tempe produced. From the test results, it was found that the controller was able to maintain an average temperature of 37.63 0C, an average humidity of 57.46%, and was able to accelerate the fermentation process of tempeh within 24 hours with an average power consumption of 212.27 Watt and used to produce tempe for small scale tempe craftsmen.